Comparison of Mutant P53 Protein Expression in Pterygium Group with and Without Triamcinolone Acetonited Injection (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Background: Mutant p53 protein is produced by mutant p53 gene, this protein takes part in tissue hyperplasia process in pterygium. Triamcinolone acetonide in often use to reduce reccurency. Besides decreasing the inflamation triamcinolone acetonide is assumed to be able to repair the function of p53 gene. Thus, it reactivates cell apoptosis system and prevent the tissue hyperplasia process in pterygium.To compare Mutant p53 Protein Expression in Pterygium Group With and Without Triamcinolone Acetonide Injection Methods: This research is a randomized clinical trial study consists of 31 subject who suffered primary pterygium. All subject divided into 2 grup with and without triamcinolone acetonide injection. After excision the pterygium and the tissue were examined through histopatology and immunohistochemical with Hematcoycline Eosin and reagent Clone DO7 staining to see the mutant p53 protein expression. Results: Mutant p53 protein expression in triamcinolone acetonite injected group is 0% and non triamcinolone acetonite injected group is 33,33% Conclusion: Mutant p53 protein expression in triamconolone acetonite injected group is lower than non injected grou.